The Production of Silver Nanoparticles and Their Effect on Sulfate Reducing Bacteria Under Steel Microbial Corrosion - Skiba, Margarita; Kurmakova, Iryna; Bondar, Olena; Demchenko, Natalia; Vorobyova, Viktoria (Видавництво Львівської політехніки, 2020)
Одержано водні дисперсії наночасток срібла внаслідок вивантаження контактної нерівноважної низькотемпературної плазми в присутності альгінату натрію (1,25–5,0 г/л). Формування часток срібла (до 100 нм) підтверджено методом рентгеноструктурного аналізу та ІЧспектроскопії. Одержані колоїдні розчини наночасток срібла сприяють формуванню менш потужної біоплівки за умов мікробної корозії низькокарбонової сталі, ініційованої сульфатвідновлювальними бактеріями роду Desulfomicrobium. Бактерії роду Desulfovibrio виявилися резистентними до наночасток срібла.

The production of silver nanoparticles was carried out in an aqueous medium treated by discharge of the contact non-equilibrium low-temperature plasma in the presence of sodium alginate (1.25–5.0 g/l). The formation of silver metal particles (to 100 nm) was confirmed by X-ray diffraction and IR spectroscopy analysis. The obtained colloidal solutions of silver nanoparticles lead to the formation of thinner biofilm under microbial corrosion of mild steel, initiated by sulfate reducing bacteria of Desulfomicrobium genus. Bacteria of Desulfovibrio genus appeared to be resistant to silver nanoparticles.
Одержання наночасток срібла та їх вплив на сульфатвідновлювальні бактерії за умов мікробної корозії сталі
Keywords: плазмохімічний; наночастки; срібло; натрій альгінат; сульфатвідновлювальні бактерії; біокорозія; plasma-chemical; nanoparticles; silver; sodium alginate; sulfate reducing bacteria; biocorrosion